Realistic Mathematics Education (RME)-Based Learning Trajectory for Arithmetic Social Using Culinary Context of Yogyakarta - Sitti Mutia Umasugi; Sugiman Sugiman; Padrul Jana; Pornphirom Kraiviset (LPPM Universitas Pendidikan Mandalika, 2022)
This study aims to analyze a learning trajectory for social arithmetic using the culinary context of Yogyakarta and the results of the retrospective analysis as an application of the hypothetical learning trajectory. The research method used was design research with three stages, namely preliminary design, teaching experiment, and retrospective analysis. The research subjects who contributed to this study were sixth elementary school graders (11-12 years old) using the purposive sampling technique. The data collection techniques were documents (written data on students' work), and participating-interview about students' thinking in mathematics during the learning process. Data analysis used retrospective analysis. The findings of this study indicate that this learning trajectory is beneficial in achieving learning objectives. The learning trajectory in this study can be considered as an alternative way or as a reference for teachers to design RME-based learning that supports the development of students' conceptual understanding, self-confidence using their strategies, communication, and reasoning skills about social arithmetic concepts. In addition, the learning process and the results of the retrospective analysis contain characteristics of Realistic Mathematics Education (RME).